Improved Understanding of k- Turbulence Model for Non-homogeneous Two-Phase Flows in Industrial Combustor - Hao, Nguyen Thanh (Engineering International, 2014)
This paper presents development of k-e turbulence model which can be applied for non-homogeneous two-phase turbulent flows. The improvement of governing equations of k-e turbulence model is based on the decomposition of the two-phase flows into the gas phase and the second phase. Thus, the turbulent kinetic energy k and the turbulent dissipation rate e variables in k-e two-equation model are substituted by the turbulent kinetic energy kg of the gas phase, the turbulent kinetic energy kp of the second phase, the turbulent dissipation rate eg of the gas phase and the turbulent dissipation rate ep of the second phase. The new turbulence model is kg-kp-eg-ep four-equation model which can be used to solve all of two-phase flows in nature studies and engineering applications.
Keywords: Turbulence model; Non-homogeneous; Two-phase flows; Turbulent kinetic energy; Turbulent dissipation rate